Cavitation in bonded natural rubber cylinders repeatedly loaded in tension - Pond T J (Journal of Natural Rubber Research, 1995)
This investigation describes cavitation behaviour in bonded rubber cylinders subjected to different loading schedules in tension. Three natural rubber vulcanisates have been studied. The effect of carbon black on cavitation behaviour is examined. It is shown that repeated cycling can alter the cavitation failure stress when compared to that of a single cycle. Some practical consequences of this finding are discussed with the mechanism of cavitation.
Keywords: Bonded Rubber Cylinders; Carbon black; Cavitation; Cycling